Water Sea Quality Study at Jakarta Bay due to Reclamtion and The Development of Giant Sea Wall (GSW) - Mardi Wibowo (Badan Geologi, 2018)
To overcome many problems in Jakarta such as: flood, tide flood, lack of water resources and land, the government decided to build a giant sea wall (GSW). Development GSW on Jakarta Bay is a form of intervention of technology on the water sea environment, so its will surely had an impact especially to the water sea quality (BOD, DO and salinity). Aim of this study is to know magnitude of sea water quality changes due to the construction of GSW .This study was conducted with computation modeling using software MIKE-2,1 Eco Lab module. Based on this study, GSW development will give significant impact to sea water quality especially waters in the formed polder. The quality of waters in formed polder significantly decreased, especially of the value of BOD . Value of BOD is rise more than 100 % and value of DO is decrease more than 20 % andsalinityis decrease more than 2 percent .To prevent a trend of decreasing the sea water quality in Jakarta Bay that caused GSW development, must be done with prevention act from upstream part before the waters entrance to Jakarta Bay.